2010 International Conference on Asian Language Processing 2010
DOI: 10.1109/ialp.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Rendering Traditional Mongolian Script

Abstract: The attached paper is a draft and reflects current research by the authors. NOTE: It is not to be distributed outside the UTC/L2 because it is intended for eventual publication. However, the authors welcome comments and questions. Please address feedback and questions to: biligsaikhan@gmail.com. Abstract. This paper discusses the rendering issues of complex text layouts, particularly traditional Mongolian script. Solving the rendering issues of complex text layouts is the key fundamental challenge to succeed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As browsers release new updates and as the Mongolian encoding model is developed, older research documents outlining issues that the Traditional Mongolian script faces become outdated. Earlier research done on this topic acknowledges the need for updated guidelines as the situation regarding Mongolian support develops (Batjargal et al, 2011). Therefore, this study can provide an updated and recent description of issues and gaps in Mongolian language support online, and can inform both computer programmers and web users of the areas of Traditional Mongolian localization that should be focused on and improved (Ishida, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As browsers release new updates and as the Mongolian encoding model is developed, older research documents outlining issues that the Traditional Mongolian script faces become outdated. Earlier research done on this topic acknowledges the need for updated guidelines as the situation regarding Mongolian support develops (Batjargal et al, 2011). Therefore, this study can provide an updated and recent description of issues and gaps in Mongolian language support online, and can inform both computer programmers and web users of the areas of Traditional Mongolian localization that should be focused on and improved (Ishida, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…This study also found that users had problems with line breaks and word wrapping for the vertical Traditional script, resulting in errors with rendering the Traditional script. Overall, the model designed for typing the Traditional script was confusing for most users surveyed (Batjargal et al, 2011).…”
Section: Useabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Grammatical rules that we applied in our approaches include, but are not limited to the followings 1) the ways of writing modern Mongolian long vowels and diphthongs in traditional Mongolian, 2) some special rules of traditional Mongolian, 3) and other rules including a) positional and variant forms; b) vowel harmony, feminine and masculine words; c) syllables and ligatures; d) closed syllable consonants; e) 'a' and 'e' in a word-final position; and f) suffixes, which were discussed in our previous study (Batjargal, Kimura, & Maeda, 2010). All above rules are utilized in our approach to translate modern Mongolian query words missing from the dictionary into traditional Mongolian.…”
Section: Ancient-to-modern Information Retrievalmentioning
confidence: 97%
“…Due to certain failures of displaying glyphs correctly (Batjargal, Kimura, & Maeda, 2010) and poor support for traditional Mongolian script at the operating system level, we implemented our approach that renders traditional Mongolian script properly, and displays vertically top-to-bottom, left-to-right on any platform and web browsers.…”
Section: Rendering Traditional Mongolian Script In the Tmsdlmentioning
confidence: 99%